Competency Development for the Secretaries of the Board of Directors of PT Pelabuhan Indonesia III (Persero) in Industrial Revolution 4.0 Era - Falda Kumala Aprilya; Suryanto Suryanto (Universitas STRADA Indonesia, 2021)
Secretaries play a particular role in supporting the company leaders to carry out their tasks.. Therefore, it is important for secretaries to continuously conduct competency development, considering that in Industrial Revolution Era 4.0 technology advancement are very likely to replace humans’ works. The writer has conducted research of competency on the Secretaries of the Board of Directors of PT Pelabuhan Indonesia III (Persero). This purpose of this research is to understand the proper competency development for the position of Secretary of the Board of Directors of PT Pelabuhan Indonesia III (Persero) in Industrial Revolution Era 4.0. This research was carried out using qualitative descriptive method by utilizing secondary or existing data. This research concluded that the competency of the Secretaries of the Board of Directors of PT Pelabuhan Indonesia III (Persero) has met the demands of Industrial Revolutio Era 4.0, although some training programs are still required.